The Construction and Comprehensive Analysis of ceRNA Networks and Tumor-Infiltrating Immune Cells in Bone Metastatic Melanoma - Huang, Runzhi; Zeng, Zhiwei; Li, Guangyu; Song, Dianwen; Yan, Penghui; Yin, Huabin; Hu, Peng; Zhu, Xiaolong; Chang, Ruizhi; Zhang, Xu; Zhang, Jie; Meng, Tong; et al. (Frontiers in Genetics, 2019)
Abstract Background/Aims: As a malignant and melanocytic tumor, cutaneous melanoma is the devastating skin tumor with high rates of recurrence and metastasis. Bone is the common metastatic location and bone metastasis may result in pathologic fracture, neurologic damage and severe bone pain. Although metastatic melanoma was reported to get benefits from immunotherapy, molecular mechanisms and immune microenviroment underlying the melanoma bone metastasis and prognostic factors are still unknown. Methods: Gene expression profiling of 112 samples including 104 primary melanomas and 8 bone metastatic melanomas from the TCGA database, were assayed to construct a ceRNA network associated with bone metastases. Besides, we detected the fraction of 22 immune cell types in melanoma via the algorithm of “cell type identification by estimating relative subsets of RNA transcripts (CIBERSORT)”. Based on the significant ceRNAs or immune cells, we constructed nomograms to predict the prognosis of patients with melanoma. Ultimately, correlation analysis was implemented to discover the relationship between the significant ceRNA and immune cells to reveal the potential signaling pathways. Results: We constructed a ceRNA network based on the interaction among 8 pairs of lncRNA-miRNA and 15 pairs of miRNA-mRNA. CIBERSORT and ceRNA integration analysis discovered that AL118506.1 has both significant prognostic value (P = 0.002) and high correlation with T follicular helper cells (P = 0.033). Meanwhile, T cells CD8 and Macrophages M2 were negatively correlated (P < 0.001). Moreover, we constructed two satisfactory nomograms (The Area Under Curve (AUC) of 3-year survival: 0.899; 5-year: 0.885 and Concordance Index: 0.780, respectively) with significant ceRNAs or immune cells, to predict the prognosis of patients. Conclusions: In this study, we suggested that bone metastasis in melanoma might be related to AL118506.1 and its role in regulating Thrombospondin 2 (THBS2) and T follicular helper cells (Tfh cells). Two nomograms were constructed to predict the prognosis of patients with melanoma and demonstrated their value in improving the personalized management.